Download presentation
Presentation is loading. Please wait.
1
R(x) is the right person L(x) is the left person.
Relay R(x) is the right person L(x) is the left person. The first person does his/her problem and then passes the answer to the partner L is the left person, R is the right person. WYR=What you receive L(x) = 1- 3x R(x) = 2x+1 R(WYR) L(5) L(5) = 1- 3(5) = 1-15 = -14 R(-14) = 2(-14)+1 = = -27 L(2) = 3(2) + 1 = 6+1 = 7 R(7) = 4(7)-2 = 26
2
L(x) = 3x + 1 R(x) = 4x - 2 L(2) R(WYR) L(2) = 3(2) + 1 = 6+1 = 7
L is the left person, R is the right person. WYR=What you receive L(x) = 3x + 1 R(x) = 4x - 2 L(2) R(WYR) L(2) = 3(2) + 1 = 6+1 = 7 R(7) = 4(7)-2 = 26
3
L(x) = 3x + 1 R(x) = 4x - 2 R(-1) L(WYR) R(-1) = 4(-1)-2 = -4 -2 = -6
L is the left person, R is the right person. WYR=What you receive L(x) = 3x + 1 R(x) = 4x - 2 R(-1) L(WYR) R(-1) = 4(-1)-2 = = -6 L(-6) = 3(-6) + 1 = =-17
4
L(x) = 3x + 1 R(x) = 4x - 2 L(4) R(WYR) L(WYR)
L is the left person, R is the right person. WYR=What you receive L(x) = 3x + 1 R(x) = 4x - 2 L(4) R(WYR) L(WYR) L(4) = 3(4) + 1 = 12+1 = 13 R(13) = 4(13)-2 = 50 L(50) = 3(50) + 1 = 151
5
L(x) = 3x2+ x+1 R(x) = -x2 +3 R(-1) L(WYR)
L is the left person, R is the right person. WYR=What you receive L(x) = 3x2+ x+1 R(x) = -x2 +3 R(-1) L(WYR) R(-1) = -(-1)2 +3 = -(-1)(-1)+3 = -1+3 = 2 L(2) = 3(2)2+2+ 1=3(2)(2)+2+1 = = 15
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.